[Rezension von: Yijiang Zhong, The origin of modern Shinto in Japan] - Andreeva, Anna (The American historical review, 2018)
The newly established Bloomsbury Shinto Studies book series continues to yield interesting research cases. Until recently in the Western imagination, Shinto was